PENGARUH PROFESIONALISME, KOMITMEN ORGANISASI DAN INDEPENDENSI TERHADAP KINERJA AUDITOR (STUDI EMPIRIS: KANTOR AKUNTAN PUBLIK JAKARTA TIMUR) - Apry Linda Diana; Desy Amaliati Setiawan (Sekolah Tinggi Pariwisata Mataram, 2022)
This study aims to determine the influence professionalism, organizational commitment and independence on the performance of auditors at public accounting firms in East Jakarta. The strategy used is associative research strategy with quantitative research methods. This study uses primary data by distributing questionnaires. The population in this study were 74 auditors who worked in the East Jakarta Regional Public Accounting Firm, while the sample in this study was 68 auditors who were determined using the non-probability method with purposive sampling technique. Data analysis used is descriptive statistics, validity and reliability tests, classical assumption test, and hypothesis testing using SPSS version 25.0 program. The results of the study show 1) Professionalism has a positive and significant influence on auditor performance at East Jakarta Public Accounting Firm, 2) Organizational commitment has a positive and significant influence on auditor performance at East Jakarta Public Accounting Firm, 3) Independence has a positive and significant influence on auditor performance at East Jakarta Public Accounting Firm.